Rola konfliktu w organizacji: The role of conflict in an organization - Kołodziejczyk, Agnieszka (Management and Administration Journal, 2021)
Recently the views on the conflicts have changed. Now it is believed that they can improve the efficiency of a company. Conflicts are the part of people’s exist in each organization, so managers should know how to manage them. This article presents the essence of conflicts in an organization, characteristic of their stages, sources, methods of conflict resolution and the role of conflict in a company